Prospects for the Use of Drugs Affecting the Protective Mechanisms of the Gastrointestinal Mucosa. The Role of Prostaglandin Production Stimulators - Ortiq o’g’li, Raupov Abdurahmon (Journal of Innovation in Education and Social Research, 2025)
Nonsteroidal anti-inflammatory drugs (NSAIDs) and acetylsalicylic acid (ASA) remain among the most widely prescribed agents worldwide, yet their use is frequently associated with gastrointestinal (GI) complications, including gastroduodenopathies and enteropathies. Traditionally, preventive strategies have focused on upper GI protection through antisecretory therapy. However, damage to the intestinal mucosa remains insufficiently addressed. Rebamipide, a novel gastro- and enteroprotective agent developed in Japan and introduced in Russia in 2016, has demonstrated high efficacy in protecting and repairing both gastric and intestinal mucosa. Its mechanism of action involves stimulation of prostaglandin synthesis, upregulation of endothelial growth factor, activation of the sonic hedgehog and ERK pathways, reduction of oxidative stress, and modulation of intestinal microbiota. Experimental and clinical studies confirm rebamipide’s ability to accelerate mucosal healing, reduce NSAID- and ASA-induced injury, inhibit H. pylori adhesion, and exert systemic anti-inflammatory effects through suppression of NF-κB and TNF-α activity. Comparative trials show that rebamipide is as effective as misoprostol but with superior tolerability and fewer gastrointestinal side effects. These findings position rebamipide as a promising pharmacological agent for comprehensive protection of the gastrointestinal tract in patients receiving long-term antiplatelet or NSAID therapy.